Red Flags of Dating Violence Among College Students: From the Perspective of Campus Service Providers in Costa Rica - Derby Munoz-Rojas; Cristobal Ching-Alvarez; Kwynn M. Gonzalez-Pons (SAGE Publishing, 2022)
Dating violence has negative consequences on the well-being of college students. Thus, it is imperative that providers of student-oriented services can detect and respond to dating violence. Although many universities worldwide have implemented dating violence screenings protocols, they are not yet common practice in Costa Rica. As a result, there is inadequate recognition of this problem, so it remains unaddressed. Therefore, this qualitative descriptive study explored the perceptions of professionals working in student-oriented services in Costa Rica about dating violence warning signs exhibited by college students. 29 providers from four public universities were interviewed, and three main areas were identified from a content analysis: the process that providers follow to identify dating violence, the visible signs that victims display, and the self-protective strategies that victims employ to hide their abuse. These findings are important for researchers and practitioners wanting to improve dating violence screening instruments for the Central American context.